'Online' integration of sensory and fear memories in the rat medial temporal lobe - Francesca S Wong; R Fred Westbrook; Nathan M Holmes (eLife, 2019)
How does a stimulus never associated with danger become frightening? The present study addressed this question using a sensory preconditioning task with rats. In this task, rats integrate a sound-light memory formed in stage 1 with a light-danger memory formed in stage 2, as they show fear when tested with the sound in stage 3. Here we show that this integration occurs ‘online’ during stage 2: when activity in the region that consolidated the sound-light memory (perirhinal cortex) was inhibited during formation of the light-danger memory, rats no longer showed fear when tested with the sound but continued to fear the light. Thus, fear that accrues to a stimulus paired with danger simultaneously spreads to its past associates, thereby roping those associates into a fear memory network.